The Influence of Professional Education and Work Motivation on The Performance of State Elementary School Teachers - Alfianita, Riani; Karnati, Neti; Supadi, Supadi; Ifnuari, Moh Reza (Journal of Education Reseach and Evaluation, 2022)
Every school continues to strive to improve the quality of education through teacher performance. Improving teacher performance is influenced by many factors, including the development of the teaching profession and work motivation. The purpose of this study was to analyze the positive influence of professional education and motivation on performance. This research was conducted on elementary school teachers with 210 civil servant teachers who had attended professional education and taught at public elementary schools in the area. The model used in this study is causal. To test the hypothesis proposed in this study, the analytical technique used is SEM (Structural Equation Modeling), which is operated through the Moment of Structural Analysis (AMOS) program. Participants in this study were civil servant teachers as many as 211 people. The selection of respondents using the Purposive Sampling Technique. The instrument used to collect data is a questionnaire. Research findings that there is a direct positive effect of professional education on performance. Work motivation has a direct positive effect on teacher performance significantly. Professional education has a positive effect on motivation. For this reason, the implementation of teacher professional education, which is the main factor in motivating teachers, needs to be maintained and controlled by conducting evaluations on a scheduled basis.